1973
DOI: 10.1039/p29730000080
|View full text |Cite
|
Sign up to set email alerts
|

Cation radicals: photochemically induced electron-transfer reactions between bipyridylium dications and formate, oxalate, and benzilate anions

Abstract: Aqueous solutions of the herbicidally active bipyridylium salts, paraquat dichloride and diquat dichloride, containing formate, oxalate, and benzilate anions undergo photoreduction to the bipyridylium cation radicals with high quantum efficiencies. Photoactivity occurs with light of wavelengths longer than can be absorbed by either oxidant or reductant, taken separately, and it is concluded that charge-transfer interaction between bipyridylium ion and carboxylate ion is the major activating influence. The thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1973
1973
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…(1) are important for our complexation studies. Although values for K , of 0.1 and 0.7 rnol dm-3 have been reported by Barnett et al (1973) and Ebbesen and Ferraudi (1983), the value of Kz in water does not appear to have been determined, We found that MV+(CI-)2 behaves as a strong electrolyte over the concentration range 2 X W2-5 X rnol dmP3, with a molar conductivity of 253 (k 2) S cmz mol-' at infinite dilution which drops to 220 (k 2) S cmz mol-' at a concentration of 1 x rnol dm-3. These molar conductivities are consistent with full dissociation of the viologen dichloride to M V + and 2C1-, and because we observed no deviations from the behaviour expected of a strong electrolyte, K2 must be greater than about 0.2 mol dm-3, which puts it in the same range as K 1 .…”
Section: Complexation Between Methyl Viologen and Chloride Ionmentioning
confidence: 90%
“…(1) are important for our complexation studies. Although values for K , of 0.1 and 0.7 rnol dm-3 have been reported by Barnett et al (1973) and Ebbesen and Ferraudi (1983), the value of Kz in water does not appear to have been determined, We found that MV+(CI-)2 behaves as a strong electrolyte over the concentration range 2 X W2-5 X rnol dmP3, with a molar conductivity of 253 (k 2) S cmz mol-' at infinite dilution which drops to 220 (k 2) S cmz mol-' at a concentration of 1 x rnol dm-3. These molar conductivities are consistent with full dissociation of the viologen dichloride to M V + and 2C1-, and because we observed no deviations from the behaviour expected of a strong electrolyte, K2 must be greater than about 0.2 mol dm-3, which puts it in the same range as K 1 .…”
Section: Complexation Between Methyl Viologen and Chloride Ionmentioning
confidence: 90%
“…This result suggests that the optimum structure of the aggregate, regarding the value of 4, exists at these concentrations. It could be argued that reaction (13), involving an intramolecular transformation, is relatively independent of aggregate structure, whilst reaction (12), being intermolecular in nature, depends subtly on the distance between the geminate pair within the aggregate. Because the highest values of @(MV'+) occur at 20mmoldm-3 MV2+ and 0.10moldm-3 EDTA, we focus our attention on the behaviour of the system under these conditions in order to understand further the properties of the species within the optimum aggregate structure.…”
Section: Discussionmentioning
confidence: 99%
“…The positive dependence of @(MV'+) on temperature suggests, although it does not prove, that + has a positive temperature coefficient; the dependences of # and 7 on temperature could be opposite, but offsetting. If d, indeed, has a positive temperature coefficient and the rate constants for reactions (12) and ( 13) can be written in the form of the usual Arrhenius expression [ k = A exp(-E,/RT)], then + = (AI3/Al2) exp(-AEIRT), where AE = EaI3 -Ea12 and Ea13 > EaI2. The unusual aspect of the results presented here then becomes the effect of the excitation wavelength on the temperature dependence and one would not expect the temperature coefficients of r) and Ea13 to exhibit such an effect.…”
Section: Discussionmentioning
confidence: 99%
“…Early work using a wide variety of phenolic compounds revealed charge transfer complexes with paraquat, for which the formation constants were small (Ledwith and Woods, 1970;White, 1969;Ebbeson and Ferraudi, 1983;Barnett et al, 1972;Kuczynski et al, 1984). The synthetic polyelectrolytes poly(styrene sulphonate), poly (vinyl sulphonate) and polymethacrylate were all found to bind paraquat by simple electrostatic attraction, in the same way that they bind alkaline earth metal ions (Baumgartner et al, 1987;Kobayashi and Niki ;.…”
mentioning
confidence: 96%